When lights turn off. Future perspectives to design smart homes - Matteo O. Ingaramo; Mila Stepanovic (Agathón)
The Covid-19 pandemic has strongly shown the uncertainty and complexity of our lives. We are involved and we participate in questioning our consolidated life models and in the experimentation of new political and economic models, involving different actors, from the governments to the communities or virtual societies. Technologies have definitely an essential role in these transformations and global challenges aimed to change. This essay analyses the link between this general phenomenon and its particular effect on private citizens, focusing on the digitisation of spaces and, in particular, domestic spaces. Challenges and emerging situations will be highlighted through some case studies concerning smart home systems, different in terms of technology and infrastructure, methods of interaction, hardware and software, and their relationship with the design of this kind of environment. In conclusion, we will present a critical approach to complex systems of the near future, to design in a more conscious and coherent way an intelligent, human-sized and sustainable environment to live in.